Effect of Different Auxins on Rooting of Semi Hard and Soft Wood Cuttings of Guava (Psidium guajava L.) CV. Safeda - Zamir, R.; Rab, Abdur; Sajid, M.; Khattak, G.S. S.; Khalil, S.A.; Shah, S.T. (The Nucleus, 2017)
An experiment was conducted to investigate the effect of different auxin on rooting in soft and semi-hard wood stem cuttings of guava. The maximum 80.3% sprouting response was recorded after 32 days of planting when soft wood cuttings were treated with 100 mg IAA/100 g talcum powder. Comparatively IAA was stronger than IBA in sprouting for both types of cuttings. The maximum number of leaves (8) was recorded in soft wood cuttings treated with IBA. The number of leaves in soft wood cuttings treated with either IBA or IAA and NAA were greater than semi hard wood cuttings. The maximum number of roots (27.6) per cutting was recorded in soft wood cuttings treated with IAA. As compared to control, auxin treatment promoted rooting in both types of cuttings. The maximum number of roots per cutting ranged from 11 to 17.3 in semi hard wood cuttings, while in soft wood cutting it ranged from 15.6 to 27.6. Irrespective of cutting type, IAA and NAA seem to be the most efficient in promoting roots. By contrast, IBA was more effective only in soft wood cuttings. The ultimate plant survival is, however, the key in such studies. In overall experiment, a maximum of 28% survival rate was recorded in soft wood cuttings when exposed to IAA at 100 mg per 100 g talcum powder combination.